Neuronal Migration Dynamics in the Developing Ferret Cortex - Gertz, Caitlyn C. (J Neurosci, 2015)
During mammalian neocortical development, newborn excitatory and inhibitory neurons must migrate over long distances to reach their final positions within the cortical plate. In the lissencephalic rodent brain, pyramidal neurons are born in the ventricular and subventricular zones of the pallium and migrate along radial glia fibers to reach the appropriate cortical layer. Although much less is known about neuronal migration in species with a gyrencephalic cortex, retroviral studies in the ferret and primate suggest that, unlike the rodent, pyramidal neurons do not follow strict radial pathways and instead can disperse horizontally. However, the means by which pyramidal neurons laterally disperse remain unknown. In this study, we identified a viral labeling technique for visualizing neuronal migration in the ferret, a gyrencephalic carnivore, and found that migration was predominantly radial at early postnatal ages. In contrast, neurons displayed more tortuous migration routes with a decreased frequency of cortical plate-directed migration at later stages of neurogenesis concomitant with the start of brain folding. This was accompanied by neurons migrating sequentially along several different radial glial fibers, suggesting a mode by which pyramidal neurons may laterally disperse in a folded cortex. These findings provide insight into the migratory behavior of neurons in gyrencephalic species and provide a framework for using nonrodent model systems for studying neuronal migration disorders. SIGNIFICANCE STATEMENT Elucidating neuronal migration dynamics in the gyrencephalic, or folded, cortex is important for understanding neurodevelopmental disorders. Similar to the rodent, we found that neuronal migration was predominantly radial at early postnatal ages in the gyrencephalic ferret cortex. Interestingly, ferret neurons displayed more tortuous migration routes and a decreased frequency of radial migration at later ages coincident with the start of cortical folding. We found that ferret neurons use several different radial glial fibers as migratory guides, including those belonging to the recently described outer radial glia, suggesting a mechanism by which ferret neurons disperse laterally. It is likely that excitatory neurons horizontally disperse in other gyrencephalic mammals, including the primate, suggesting an important modification to the current model deduced primarily from the rodent.